1994
DOI: 10.1177/875608799401000303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vitamin E, Irganox 1010 and Bht as Antioxidants On Release of Off-Flavor From Hdpe Bottles

Abstract: The effects of vitamin E, Irganox 1010, and BHT as antioxidants for reducing the release of off-flavor (both off-odor and off-taste) from blow- molded HDPE bottles were investigated. A sensory study was conducted and showed that bottles containing vitamin E had a lower odor intensity and a higher acceptability for storage of drinking water compared to bottles contain ing Irganox 1010 or BHT. Forty-seven volatile compounds were identified to release from the bottles using the purge-and-trap GC/MS analysis. Thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…As a result of these considerations, there is a growing interest in using a-tocopherol (ie vitamin E) as an alternative antioxidant for polymer stabilisation. 4 Ho et al 4 have shown a-tocopherol to be more effective at lower levels than those required for antioxidants such as Irganox 1010 and BHT in reducing the off-¯avour from blowmoulded HDPE bottles. On the other hand, Bailey 1 showed that the rate of loss of BHT from multilayer coextrusion ®lm structures was much greater than the rate of loss of a-tocopherol under the same storage conditions.…”
Section: Introductionmentioning
confidence: 98%
“…As a result of these considerations, there is a growing interest in using a-tocopherol (ie vitamin E) as an alternative antioxidant for polymer stabilisation. 4 Ho et al 4 have shown a-tocopherol to be more effective at lower levels than those required for antioxidants such as Irganox 1010 and BHT in reducing the off-¯avour from blowmoulded HDPE bottles. On the other hand, Bailey 1 showed that the rate of loss of BHT from multilayer coextrusion ®lm structures was much greater than the rate of loss of a-tocopherol under the same storage conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Table 1 gives the amounts of antioxidant migrated from the LLDPE film after one day of incubation at different temperatures for the 55% and 100% ethanolic solutions. The diffussion coefficients D were calculated for each temperature using equation (2). Table 1 shows that the diffusion coefficients of the antioxidants increase with increasing temperature for both the 55% ethanolic simulant and 100% ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Butylated hydroxytoluene (BHT), Irganox 1076 and 1010 are commonly used hindered phenolic antioxidants often in combination with Irgafos 168, for reducing the formation of undesirable oxidative compounds during polymer processing. These antioxidants are usually used at concentrations up to 500 ppm 2,4 and are able to migrate into foods. Ethanolic food simulating liquids have been used as simulants for fatty foods, 5,6 particularly when analytical difficulties occur with the conventional fat simulants, such as olive oil or sunflower oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Laermer et al (1996) showed that addition of vitamin E to high density polyethylene (HDPE)-ethylene/vinyl acetate (EVA)-HDPE flexible packaging system could reduce the ''plastic'' taste and preserve the fresh taste of breakfast cereals. Ho et al (1994) showed that vitamin E was effective in reducing off-flavor compounds released from HDPE bottles. Vitamin E has somehow superior antioxidant behavior than BHT related to the off-flavor generation, stability and solubility, in polyolefins.…”
Section: Othersmentioning
confidence: 99%